4R history and recent phosphorus research. Issue 2 (22nd March 2018) - Flis, Sally
Abstract : Where did the 4R idea come from? This article looks at a few of the early sources and how those concepts relate to current challenges facing phosphorus management. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/564 .